Medidas de impedância elétrica em água Milli-Q e difusão anômala - Rodrigues, Thiago Petrucci (2013)
The objective of this work is to investigate the behavior of the electrical response obtained for Milli-Q water with impedance spectroscopy technique and understand the results through the diffusion equation of fractional order. The experiments are performed with steel and brass electrodes and the results are compared with the theoretical model. We obtained a good fit throughout frequency spectrum, based on fractional calculation, and the behavior of curves suggests that in low frequency the ions in the sample have an anomalous diffusion.